2016
DOI: 10.1097/bth.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship of Trabecular Metal Anchored Glenoid Total Shoulder Arthroplasties

Abstract: Trabecular metal anchored glenoids (TMAGs) were developed to counter the pervasive problem of component loosening at the bone-cement interface in total shoulder arthroplasty. Increased failure rates associated with the glenoid component have been previously reported due to increased rates of glenoid failures. Our hypothesis was that in our patients, the failure rate of TMAG implants is similar to or less than reported failure rates of traditional all polyethylene glenoid components. A medical chart review of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…1). The final cemented PEG group included 3312 patients (25 articles) , and the modern MBG group included 457 patients (10 articles) [4][5][6][37][38][39][40][41][42][43].…”
Section: Search Resultsmentioning
confidence: 99%
“…1). The final cemented PEG group included 3312 patients (25 articles) , and the modern MBG group included 457 patients (10 articles) [4][5][6][37][38][39][40][41][42][43].…”
Section: Search Resultsmentioning
confidence: 99%
“…Among those, 62 duplicate articles were identified and removed from the search. Following elimination of duplicate articles and predetermined exclusion criteria, seven articles were included for analysis 19–25 (Figure 1).
Figure 1.Flow chart of study selection according to PRISMA guidelines for reporting systematic reviews and meta-analyses.
…”
Section: Resultsmentioning
confidence: 99%
“…Among those, 62 duplicate articles were identified and removed from the search. Following elimination of duplicate articles and predetermined exclusion criteria, seven articles were included for analysis [19][20][21][22][23][24][25] (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term clinical studies investigating the performance of the second generation TM glenoid have yielded good to excellent patient outcomes; however, the majority of these studies only reported outcomes at a minimum two-year follow-up. 9,[13][14][15][16] Furthermore, short-term reports of radiographic metal debris formation associated with these components have shed a cautionary light and raised concern for possible future implant failure. 14,16 In the current literature, five-year or greater follow-up outcomes of the second generation TM glenoid are lacking and the true rate of metal debris formation at mid-to long-term is unknown.…”
Section: Introductionmentioning
confidence: 99%